2018
DOI: 10.1177/0886260518760019
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Children’s Trauma Symptoms Following Complex Trauma Exposure

Abstract: Complex trauma exposure has been defined as multiple or chronic interpersonal trauma that begins early in life, which leads to widespread dysregulation. Previous studies have reported that minorities may be at greater risk for trauma exposure and symptoms; yet, racial differences have not been investigated in the context of complex trauma. The aim of the present study was to determine if there are racial disparities in children's trauma exposure and outcomes among 167 child survivors of complex trauma (3-18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Although psychophysiological processes (e.g., fight/flight/freeze/submit) are involved in post-traumatic reactions and although these phenomena can be observed even in other animals (Bradshaw et al, 2008; Nijenhuis et al, 1998; Ross et al, 2017; Van der Kolk, 2014), social and cultural factors may also affect the impacts of trauma and the manifestations of post-traumatic reactions. For example, it has been found that culture could affect the autobiographical memory of trauma (Jobson & O’Kearney, 2006), and the prevalence of and stigma associated with PTSD (Asnaani & Hall-Clark, 2017), as well as the disclosure of trauma experiences and trauma-related difficulties (Wamser-Nanney et al, 2021). However, most of the reviewed studies were conducted in Western cultures—only four studies were conducted in Asia, and no study was conducted in Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although psychophysiological processes (e.g., fight/flight/freeze/submit) are involved in post-traumatic reactions and although these phenomena can be observed even in other animals (Bradshaw et al, 2008; Nijenhuis et al, 1998; Ross et al, 2017; Van der Kolk, 2014), social and cultural factors may also affect the impacts of trauma and the manifestations of post-traumatic reactions. For example, it has been found that culture could affect the autobiographical memory of trauma (Jobson & O’Kearney, 2006), and the prevalence of and stigma associated with PTSD (Asnaani & Hall-Clark, 2017), as well as the disclosure of trauma experiences and trauma-related difficulties (Wamser-Nanney et al, 2021). However, most of the reviewed studies were conducted in Western cultures—only four studies were conducted in Asia, and no study was conducted in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…and the manifestations of post-traumatic reactions. For example, it has been found that culture could affect the autobiographical memory of trauma (Jobson & O'Kearney, 2006), and the prevalence of and stigma associated with PTSD (Asnaani & Hall-Clark, 2017), as well as the disclosure of trauma experiences and trauma-related difficulties (Wamser-Nanney et al, 2021). However, most of the reviewed studies were conducted in Western cultures-only four studies were conducted in Asia, and no study was conducted in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma-informed approaches may be helpful in reducing justice-system contact given the encouraging evidence-base of trauma treatment reducing problem behaviors. This may be a meaningful step in creating treatment parity between non-White youth and White youth in light of racial/ethnic differences in trauma exposure, symptoms, and treatment (López et al, 2017; Stolbach & Anam, 2017; Wamser-Nanney et al, 2021). Additional research is needed to discern the effects of trauma treatment and access to treatment among non-White youth compared with their White counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Black youth are at an increased risk for ACEs, as they are disproportionality represented in high-risk environments, such as juvenile detention centers, low-income communities, and foster-care placements (Wamser-Nanney et al, 2018). Furthermore, Black 75 Although retrospective recall of perceptions of an event would have the same limitations as other items in ACE measurement (i.e., inaccurate representations of past events due to memory recall factors; Frazier et al, 2011), future research may provide preliminary support to include perceptions of ACEs in screening measures.…”
Section: Implications and Future Directionsmentioning
confidence: 99%